2018
DOI: 10.22146/jpsi.32341
|View full text |Cite
|
Sign up to set email alerts
|

Keterlibatan Orang Tua terhadap Keterampilan Sosial Siswa Berkebutuhan Khusus di Sekolah Dasar Inklusif

Abstract: This study aims to examine the relationship between parental involvement and social skills of students with SEN in inclusive elementary primary. It also examines student factors, namely gender, types of disability, and level of impairment that can affect student's social skills. Participants were 365 parents of students with Special Educational Need (SEN) in inclusive elementary school. Parental involvement was measured using the Family Involvement Questionnaire. Students' social skills assessed using the Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
1
4
1
8
Order By: Relevance
“…The result demonstrates that there was no difference in social skills scores between male and female students in this study. This result contradicts the claim of Mangunsong and Wahyuni (2018) that male students tend to show significantly higher social skills than female students. Yet, a study by Epley (2009) revealed that girls tend to have better social skills than boys.…”
Section: Resultscontrasting
confidence: 95%
See 3 more Smart Citations
“…The result demonstrates that there was no difference in social skills scores between male and female students in this study. This result contradicts the claim of Mangunsong and Wahyuni (2018) that male students tend to show significantly higher social skills than female students. Yet, a study by Epley (2009) revealed that girls tend to have better social skills than boys.…”
Section: Resultscontrasting
confidence: 95%
“…The data suggest that the more support special needs students received from their families, the better their social skills will be. This is in line with research conducted by Mangunsong and Wahyuni (2018) which states that parental involvement is positively correlated with the social skills of students with special needs. Similarly, Bennett and Hay (2007) also found that healthy family relationship makes greater development of children's social skill.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Orangtua memiliki peran yang sangat penting dalam mendidik anak utamanya pada anak berkebutuhan khusus karena orangtua perlu untuk membantu mengajarkan anak mempelajari keterampilan-keterampilan tertentu yang nantinya diperlukan anak ketika dewasa untuk hidup mandiri (Mangunsong & Wahyuni, 2018). Hal ini didukung oleh penelitian dari Mangunsong dan Wahyuni (2018) yang memberikan hasil bahwa terdapat hubungan yang signifikan antara keterlibatan orangtua dengan keterampilan siswa berkebutuhan khusus, di mana semakin orangtua terlibat dalam proses pendidikan anaknya maka semakin tinggi pula keterampilan sosial yang dimiliki oleh anak (p < .01).…”
Section: Syafira Nur Sabillaunclassified